Corrosion-resistant aluminum alloy plate for new energy automobile battery and preparation process of corrosion-resistant aluminum alloy plate

By adding specific elements to aluminum alloy sheets and adopting improved preparation processes, combined with the coating liquid modified lubricant, the corrosion and friction wear problems of aluminum alloy sheets in new energy vehicle batteries are solved, and a higher level of Corrosion resistance and surface quality.

CN119392056AInactive Publication Date: 2025-02-07广东红荔枝新材料科技有限公司
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411688512.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The aluminum alloy plates used in new energy vehicle batteries are prone to corrosion in complex working environments, and the friction between the tool and the alloy is relatively large during the pressing process, which affects the appearance quality and assembly accuracy.

Method used

Using specific components of aluminum alloy sheets, including elements such as Si, Mg, Mn, Re, Sc and La, through specific smelting and preparation processes, corrosion-resistant aluminum alloy sheets are formed, and a lubricant modified with a coating liquid is used to Reduce tool friction with alloy.

Benefits of technology

It significantly improves the corrosion resistance and surface smoothness of aluminum alloy sheets, reduces friction and wear during pressing, and improves the overall performance and aesthetics of battery materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to a corrosion-resistant aluminum alloy plate for a new energy automobile battery and a preparation process of the corrosion-resistant aluminum alloy plate, and belongs to the technical field of alloys, the aluminum alloy plate comprises the following components in percentage by mass: 0.50-1.00 wt% of Si, 1.80-2.20 wt% of Mg, 1.10-1.20 wt% of Mn, 0.5-1.0 wt% of Re, 0.15-0.20 wt% of Sc, 0.60-1.20 wt% of La, less than or equal to 0.05 wt% of inevitable impurities and the balance of Al. The corrosion resistance of the aluminum alloy plate is improved through the synergistic effect of manganese, rhenium, magnesium and lanthanum, meanwhile, the lubricant is self-made and is used for preparing the aluminum alloy plate, abrasion of a tool to alloy in the pressing process can be reduced, the quality of the aluminum alloy plate finished product is improved, and the surface attractiveness of the aluminum alloy plate finished product is also improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of alloys, and in particular, relates to a corrosion-resistant aluminum alloy plate for new energy vehicle batteries and a preparation process thereof. Background Art

[0002] With the increasing attention paid to environmental protection and sustainable development around the world, the new energy vehicle industry has ushered in an opportunity for vigorous development. As the core component of new energy vehicles, the performance of batteries directly affects the mileage, safety and service life of the entire vehicle. In order to meet the demand for high-performance batteries in new energy vehicles, the selection of battery materials is crucial. Aluminum alloy sheets are widely used in the manufacture of new energy vehicle batteries due to their good electrical conductivity, thermal conductivity and light weight. However, in actual application, the working environment faced by new energy vehicle batteries is relatively complex, and they are often exposed to various harsh conditions and are prone to corrosion. This puts extremely high demands on the corrosion resistance of aluminum alloy sheets used for batteries. At the same time, in the manufacturing process of new energy vehicle battery components, aluminum alloy sheets are usually required to be pressed and other processing processes to form them into a shape that meets the design requirements. However, during the pressing process, a large friction force will be generated between the aluminum alloy material and the pressing tool, which will eventually affect the appearance quality of the aluminum alloy material used for the battery and reduce the beauty of the product; in addition, wear will also change the surface roughness and dimensional accuracy of the aluminum alloy sheet, affecting the subsequent assembly accuracy and product performance.

[0003] Therefore, developing a corrosion-resistant aluminum alloy sheet for new energy vehicle batteries and its preparation process to solve the above problems, improve the comprehensive performance of aluminum alloy sheets, and meet the growing demand for battery materials in the new energy vehicle industry has important practical significance and broad market prospects. Summary of the invention

[0004] The purpose of the present invention is to provide a corrosion-resistant aluminum alloy plate for new energy vehicle batteries and a preparation process thereof, which solves the problems of poor corrosion resistance and large wear of the alloy by tools during the pressing process in the prior art.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A corrosion-resistant aluminum alloy sheet for new energy vehicle batteries, wherein the aluminum alloy sheet comprises the following components by mass percentage: Si: 0.50-1.00wt%, Mg: 1.80-2.20wt%, Mn: 1.10-1.20wt%, Re: 0.5-1.0wt%, Sc: 0.15-0.20wt%, La: 0.60-1.20wt%, unavoidable impurities ≤0.05wt%, and the balance is Al.

[0006] The preparation process of corrosion-resistant aluminum alloy plates for new energy vehicle batteries specifically includes the following steps: S1. According to the composition and proportion of the above aluminum alloy sheet, industrial aluminum ingot (99.95wt.%), magnesium ingot (99.99wt.%), Al-10wt.%Si master alloy, Al-15wt.%Mn master alloy, Al-2.0wt.%Sc master alloy, Al-10wt.%La master alloy, Al-10wt.%Re master alloy were weighed, and the surface oxide scale was removed, dried, and preheated respectively; S2, the furnace body is temperature-controlled to add the preheated industrial aluminum ingot and Al-15wt.%Mn master alloy, and the alloy is melted and kept warm. After the insulation is completed, the furnace body is temperature-controlled to add Al-10wt.%Si master alloy, Al-2.0wt.%Sc master alloy, Al-10wt.%La master alloy and Al-10wt.%Re master alloy, and the alloy is melted and kept warm for the second time. The furnace body temperature is maintained, and the magnesium ingot wrapped in aluminum foil is added to melt to obtain alloy liquid; S3, the alloy liquid is subjected to slagging, refining, degassing, temperature control and heat preservation, and the alloy liquid is cast into a preheated warm mold, cooled, taken out and air-cooled to obtain an intermediate alloy; S4. Grind the surface of the intermediate alloy, apply lubricant at room temperature and heat it for insulation. After the insulation is completed, use a hydraulic press to press the intermediate alloy according to customer requirements to obtain the finished aluminum alloy sheet.

[0007] As a preferred technical solution of the present invention, the temperature of the first temperature control of the furnace in step S2 is 730-740°C; the temperature of the first melting and insulation is 20-30min; the temperature of the second temperature control is 700-710°C; the temperature of the second melting and insulation is 20-30min.

[0008] As a preferred technical solution of the present invention, the smelting process in step S2 is protected by argon gas.

[0009] As a preferred technical solution of the present invention, the temperature of the temperature control and insulation in step S3 is 695-700°C, and the time is 30-40 minutes; the cooling time is 10-15 minutes.

[0010] As a preferred technical solution of the present invention, the heating and heat preservation in step S4 is heating to 680-700° C. and heat preservation for 20-40 minutes; the coating thickness of the lubricant is 0.1-0.2 mm.

[0011] As a preferred technical solution of the present invention, the preparation process of the lubricant in step S4 is: A1, formamide and dopamine hydrochloride are mixed uniformly and stirred once, after the stirring is completed, N, N-diethylethylamine is added and stirred twice, hexadecane bromide is added and stirred three times, the pH value of the solution is adjusted, deionized water is added, filtered, the filter residue is washed, trishydroxymethylaminomethane hydrochloride and coconut oil fatty acid diethanolamide are added to the washed filter residue, mixed uniformly and ultrasonically stirred to obtain a coating solution; A2, mixing aluminum sol, silica sol and deionized water uniformly and stirring, filtering, taking the filter residue for washing, to obtain a mixture A, mixing the mixture A and anhydrous ethanol uniformly and stirring, temperature-controlled hydrothermal treatment, cooling, to obtain a mixture B; A3, mixing the coating liquid and the mixed material B, stirring, filtering, taking the filter residue and washing it with deionized water for 3-5 times to obtain composite particles; A4. Mix the base oil, composite particles and surfactant, stir for 20-30 minutes and then ultrasonically oscillate for 20-30 minutes to obtain a lubricant.

[0012] As a preferred technical solution of the present invention, the dosage ratio of dimethylformamide, dopamine hydrochloride, N,N-diethylethylamine, hexadecane bromide, deionized water, trishydroxymethylaminomethane hydrochloride and coconut oil fatty acid diethanolamide in step A1 is 3-3.2mL: 0.2-0.3g: 0.2-0.22mL: 0.5-0.55mL: 2-2.5mL: 100-110mL: 2-3mL.

[0013] As a preferred technical solution of the present invention, the time for the first stirring and the second stirring in step A1 is 30-40 minutes; the adding of hexadecane bromide and stirring three times is specifically adding hexadecane bromide at a rate of 1 drop / s and stirring for 4-4.5 hours; the pH of the solution is adjusted to 3-4 using 0.1 mol / L hydrochloric acid solution; the washing is washing with deionized water for 3-5 times; the pH of the tris(hydroxymethyl)aminomethane hydrochloride) is 8; and the ultrasonic stirring time is 15-30 minutes.

[0014] As a preferred technical solution of the present invention, the mass ratio of the aluminum sol, silica sol and deionized water in step A2 is 1.5-2:1:2.5-3; the mass ratio of the mixture A and anhydrous ethanol is 1:150-160mL.

[0015] As a preferred technical solution of the present invention, the stirring time in step A2 is 20-30 minutes; the filter residue washing is washing the filter residue with deionized water and anhydrous ethanol for 2-3 times respectively; the temperature of the temperature-controlled hydrothermal treatment is 200-210°C, and the time is 2-3 hours; the cooling is cooling to room temperature.

[0016] As a preferred technical solution of the present invention, the dosage ratio of the coating liquid and the mixed material B in step A3 is 100-105mL:1-1.2g.

[0017] As a preferred technical solution of the present invention, the stirring time in step A3 is 22-24 hours; and the filter residue washing is washing the filter residue with deionized water for 3-5 times.

[0018] As a preferred technical solution of the present invention, the mass ratio of the base oil, the composite particles and the surfactant in step A4 is 93-96:3-5:1-2.

[0019] Furthermore, the base oil in step A4 includes EOT5# machinery oil purchased from Shanghai Hastai Lubricant Co., Ltd., and EOT5# machinery oil does not contain other additives such as sulfur, phosphorus and chlorine; and the surfactant includes dodecylphenol polyoxyethylene ether.

[0020] Beneficial effects of the present invention: (1) The manganese element added in the present invention can increase the nucleation rate to achieve the effect of grain refinement, the rhenium element added can effectively reduce the potential difference, the magnesium element added can delay the eutectoid transformation process of the alloy, and the lanthanum element added can improve the grain boundary state of the system and offset the adverse effects of impurity elements on the corrosion performance of the alloy; that is, the four elements can synergistically increase the corrosion resistance of the aluminum alloy plate from different dimensions.

[0021] (2) The present invention uses hexadecane bromide, dopamine hydrochloride and coconut oil fatty acid diethanolamide as the main raw materials to prepare a coating liquid, and then washes, hydrothermally treats, and then coats and modifies with the coating liquid after mixing aluminum sol and silica sol to obtain composite particles whose chemical components are mainly aluminum oxide and silicon dioxide. Because silicon dioxide has the characteristics of both inorganic and organic molecular chains, it can fill the tiny pits on the metal surface, making the surface smoother and enhancing lubrication; aluminum oxide can form a protective film on the metal surface, reducing the wear of the metal surface; because mixing aluminum sol and silica sol can combine the functions of the two raw materials, the lubricating and friction-reducing effects of the lubricant are synergistically increased; At the same time, due to the presence of hexadecane bromide in the coating liquid, the compatibility of the composite particles with EOT5# machine oil is increased, and the presence of dopamine hydrochloride can form steric hindrance between the composite particles, reducing the interaction between the composite particles. On this basis, in order to further stabilize and disperse the composite particles, coconut oil fatty acid diethanolamide is added to assist and help reduce the agglomeration of the composite particles. In addition, coconut oil fatty acid diethanolamide can also provide certain extreme pressure and wear resistance, which helps to increase the anti-wear and lubricating effect of the lubricant, thereby reducing the wear of the tool on the intermediate alloy during the pressing process, reducing the surface wear marks of the finished aluminum alloy sheet, improving the quality of the finished aluminum alloy sheet, and increasing its surface aesthetics. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] The aluminum sol used in the present invention is nano-grade, with the brand name XD-LA20WR, purchased from Wuhu Xinda New Material Technology Co., Ltd.; the silica sol used is nano-grade, with the brand name HS830, purchased from Guangdong Huierte Nanotechnology Co., Ltd.; the above will not be repeated in the following.

[0024] Example 1 Prepare a lubricant, the preparation process of the lubricant is: A1, formamide and dopamine hydrochloride were mixed and stirred for 40 minutes, N, N-diethylethylamine was added after stirring, and stirred for 30 minutes, brominated hexadecane was added at a rate of 1 drop / s and stirred for 4 hours, 0.1 mol / L hydrochloric acid solution was used to adjust the pH to 3, deionized water was added, filtered, the filter residue was washed with deionized water for 4 times, tris(hydroxymethyl)aminomethane hydrochloride) and coconut oil fatty acid diethanolamide were added to the washed filter residue, the mixture was mixed and ultrasonically stirred for 15 minutes to obtain a coating solution; The dosage ratio of the dimethylformamide, dopamine hydrochloride, N,N-diethylethylamine, hexadecane bromide, deionized water, tris(hydroxymethyl)aminomethane hydrochloride and coconut oil fatty acid diethanolamide is 3.1 mL: 0.25 g: 0.2 mL: 0.55 mL: 2 mL: 100 mL: 2 mL; A2, aluminum sol, silica sol and deionized water were mixed and stirred for 20 minutes, filtered, and the filter residue was washed twice with deionized water and anhydrous ethanol respectively to obtain a mixture A, and the mixture A and anhydrous ethanol were mixed and stirred for 25 minutes, and the mixture was hydrothermally treated at 200° C. for 2 hours, and cooled to room temperature to obtain a mixture B; The mass ratio of the aluminum sol, silica sol and deionized water is 1.5:1:2.75; the mass ratio of the mixture A and anhydrous ethanol is 1:150mL; A3, the coating liquid and the mixed material B are mixed and stirred for 23 hours, filtered, and the filter residue is washed with deionized water for 3-5 times to obtain composite particles; The dosage ratio of the coating liquid to the mixed material B is 105 mL:1.2 g; A4, mixing EOT5# machine oil, composite particles and dodecylphenol polyoxyethylene ether, stirring for 20 minutes and then ultrasonically oscillating for 20 minutes to obtain a lubricant; The mass ratio of the base oil, the composite particles and the surfactant is 93:5:1.

[0025] Example 2 Prepare a lubricant, the preparation process of the lubricant is: A1, formamide dimethylamine and dopamine hydrochloride were mixed and stirred for 35 minutes, N, N-diethylethylamine was added after stirring and stirred for 35 minutes, brominated hexadecane was added at a rate of 1 drop / s and stirred for 4 hours, 0.1 mol / L hydrochloric acid solution was used to adjust the pH to 3.5, deionized water was added, filtered, the filter residue was washed with deionized water for 3 times, tris(hydroxymethyl)aminomethane hydrochloride) and coconut oil fatty acid diethanolamide were added to the washed filter residue, pH=8, mixed and ultrasonically stirred for 22.5 minutes to obtain a coating solution; The dosage ratio of the dimethylformamide, dopamine hydrochloride, N,N-diethylethylamine, hexadecane bromide, deionized water, tris(hydroxymethyl)aminomethane hydrochloride and coconut oil fatty acid diethanolamide is 3mL:0.3g:0.21mL:0.5mL:2.5mL:105mL:2.5mL; A2, aluminum sol, silica sol and deionized water were mixed and stirred for 30 minutes, filtered, and the filter residue was washed with deionized water and anhydrous ethanol for 2 times to obtain a mixture A, and the mixture A and anhydrous ethanol were mixed and stirred for 20 minutes, and the mixture was hydrothermally treated at 210° C. for 3 hours, and cooled to room temperature to obtain a mixture B; The mass ratio of the aluminum sol, silica sol and deionized water is 1.75:1:2.5; the mass ratio of the mixture A and anhydrous ethanol is 1:155mL; A3, the coating liquid and the mixed material B are mixed and stirred for 22 hours, filtered, and the filter residue is washed with deionized water for 3-5 times to obtain composite particles; The dosage ratio of the coating liquid to the mixed material B is 102.5 mL:1.1 g; A4, mixing EOT5# machine oil, composite particles and dodecylphenol polyoxyethylene ether, stirring for 30 minutes and then ultrasonically oscillating for 25 minutes to obtain a lubricant; The mass ratio of the base oil, the composite particles and the surfactant is 94.5:3:1.5.

[0026] Example 3 Prepare a lubricant, the preparation process of the lubricant is: A1, formamide and dopamine hydrochloride were mixed and stirred for 30 minutes, N, N-diethylethylamine was added after stirring and stirred for 40 minutes, hexadecane bromide was added at a rate of 1 drop / s and stirred for 4.5 hours, 0.1 mol / L hydrochloric acid solution was used to adjust the pH to 4, deionized water was added, filtered, the filter residue was washed with deionized water for 5 times, tris(hydroxymethyl)aminomethane hydrochloride) and coconut oil fatty acid diethanolamide were added to the washed filter residue, pH=8, mixed and ultrasonically stirred for 30 minutes to obtain a coating solution; The dosage ratio of the dimethylformamide, dopamine hydrochloride, N,N-diethylethylamine, hexadecane bromide, deionized water, trishydroxymethylaminomethane hydrochloride and coconut oil fatty acid diethanolamide is 3.2mL:0.2g:0.22mL:0.54mL:2.2mL:110mL:3mL; A2, aluminum sol, silica sol and deionized water were mixed and stirred for 25 minutes, filtered, and the filter residue was washed with deionized water and anhydrous ethanol for 3 times to obtain a mixture A, and the mixture A and anhydrous ethanol were mixed and stirred for 30 minutes, and the mixture was hydrothermally treated at 205° C. for 3 hours, and cooled to room temperature to obtain a mixture B; The mass ratio of the aluminum sol, silica sol and deionized water is 2:1:3; the mass ratio of the mixture A and anhydrous ethanol is 1:160mL; A3, the coating liquid and the mixed material B are mixed and stirred for 24 hours, filtered, and the filter residue is washed with deionized water for 3-5 times to obtain composite particles; The dosage ratio of the coating liquid to the mixed material B is 100mL:1g; A4, mixing EOT5# machine oil, composite particles and dodecylphenol polyoxyethylene ether, stirring for 25 minutes and then ultrasonically oscillating for 30 minutes to obtain a lubricant; The mass ratio of the base oil, the composite particles and the surfactant is 96:4:2.

[0027] Comparative Example 1 Compared with Example 3, the difference is that dopamine hydrochloride is not added in step A1 of Comparative Example 1, and the other operating steps and parameters remain unchanged.

[0028] Comparative Example 2 Compared with Example 3, the difference is that in step A1 of Comparative Example 2, hexadecane bromide is not added, and the other operating steps and parameters remain unchanged.

[0029] Comparative Example 3 Compared with Example 3, the difference is that coconut oil fatty acid diethanolamide is not added in step A1 of comparative example 3, and the other operating steps and parameters remain unchanged.

[0030] Comparative Example 4 Compared with Example 3, the difference is that in step A2 of Comparative Example 4, the silica sol is replaced by aluminum sol of the same mass, and the other operating steps and parameters remain unchanged.

[0031] Comparative Example 5 Compared with Example 3, the difference is that in step A2 of Comparative Example 5, the aluminum sol is replaced by silica sol of the same mass, and the other operating steps and parameters remain unchanged.

[0032] Example 4 A corrosion-resistant aluminum alloy sheet for new energy vehicle batteries, wherein the aluminum alloy sheet comprises the following components by mass percentage: Si: 1.00wt%, Mg: 2.00wt%, Mn: 1.00wt%, Re: 1.0wt%, Sc: 0.20wt%, La: 1.20wt%, inevitable impurities ≤ 0.05wt%, balance Al; The preparation process of corrosion-resistant aluminum alloy plates for new energy vehicle batteries specifically includes the following steps: S1. According to the composition and proportion of the above aluminum alloy sheet, industrial aluminum ingot (99.95wt.%), magnesium ingot (99.99wt.%), Al-10wt.%Si master alloy, Al-15wt.%Mn master alloy, Al-2.0wt.%Sc master alloy, Al-10wt.%La master alloy, Al-10wt.%Re master alloy were weighed, and the surface oxide scale was removed, dried, and preheated respectively; S2, the furnace body is controlled to 735 ° C for the first time, and the preheated industrial aluminum ingot and Al-15wt.%Mn master alloy are added, and the melting is carried out and the heat preservation is carried out for 30 minutes. After the heat preservation is completed, the furnace body is controlled to 710 ° C for the second time, and Al-10wt.%Si master alloy, Al-2.0wt.%Sc master alloy, Al-10wt.%La master alloy and Al-10wt.%Re master alloy are added, and the secondary melting is carried out and the heat preservation is carried out for 30 minutes. The furnace body temperature is maintained, and the magnesium ingot wrapped in aluminum foil is added, and the alloy liquid is obtained; Wherein, the above smelting process adopts argon protection; S3, the alloy liquid is subjected to slagging, refining, and degassing, and the temperature is controlled at 698°C for 30 minutes, and the alloy liquid is cast into a preheated warm mold, cooled for 15 minutes, taken out and air-cooled to obtain an intermediate alloy; S4, grinding the surface of the master alloy, coating it with 0.2 mm thick lubricant prepared in Example 2 at room temperature, heating it to 690° C. and keeping it warm for 40 min, and after the insulation is completed, using a hydraulic press to press the master alloy according to customer requirements to obtain a finished aluminum alloy sheet.

[0033] Example 5 Compared with Example 4, the difference is that in Example 5: (1) The aluminum alloy plate comprises the following components by mass percentage: Si: 0.75wt%, Mg: 2.20wt%, Mn: 1.10wt%, Re: 0.5wt%, Sc: 0.18wt%, La: 0.60wt%, inevitable impurities ≤ 0.05wt%, balance Al; (2) In step S2: the temperature of the first temperature control is 740°C, the temperature of the first melting and heat preservation is 25 minutes, the temperature of the second temperature control is 700°C, the temperature of the second melting and heat preservation is 20 minutes; (3) In step S3: control the temperature to 695°C for 35 min, and cool for 12.5 min; (4) Step S4: After polishing, the lubricant prepared in Example 1 was coated with 0.1 mm at room temperature and heated to 700 ° C for 30 min; The remaining operation steps and parameters remain unchanged.

[0034] Example 6 Compared with Example 4, the difference is that in Example 6: (1) The aluminum alloy plate comprises the following components by mass percentage: Si: 1.00wt%, Mg: 2.00wt%, Mn: 1.00wt%, Re: 1.0wt%, Sc: 0.20wt%, La: 1.20wt%, inevitable impurities ≤ 0.05wt%, balance Al; (2) In step S2: the temperature of the first temperature control is 735°C, the temperature of the first melting and heat preservation is 30 minutes, the temperature of the second temperature control is 710°C, the temperature of the second melting and heat preservation is 30 minutes; (3) In step S3: control the temperature at 698°C for 30 min, and cool for 15 min; (4) Step S4: After polishing, the lubricant prepared in Example 2 was coated with 0.15 mm at room temperature and heated to 690 ° C for 40 min; The remaining operation steps and parameters remain unchanged.

[0035] Comparative Examples 6-10 Compared with Example 4, the difference is that the lubricant prepared in Example 2 in step S4 of Comparative Examples 6-10 is replaced by the lubricant prepared in Comparative Examples 1-5 respectively, and the other operating steps and parameters remain unchanged.

[0036] Comparative Example 11 Compared with Example 4, the difference of Comparative Example 11 is that the aluminum alloy plate does not include the Mg element, and includes the following components by mass percentage: Si: 1.00wt%, Mn: 1.67wt%, Re: 1.67wt%, Sc: 0.20wt%, La: 1.86wt%, unavoidable impurities ≤ 0.05wt%, and the balance is Al; the other operating steps and parameters remain unchanged.

[0037] Comparative Example 12 Compared with Example 4, the difference of Comparative Example 12 is that the aluminum alloy plate does not include the Mn element, and includes the following components by mass percentage: Si: 0.75wt%, Mg: 2.33wt%, Re: 1.34wt%, Sc: 0.18wt%, La: 1.53wt%, unavoidable impurities ≤ 0.05wt%, and the balance is Al; the other operating steps and parameters remain unchanged.

[0038] Comparative Example 13 Compared with Example 4, the difference of Comparative Example 13 is that the aluminum alloy plate does not include Re element, and includes the following components by mass percentage: Si: 0.75wt%, Mg: 2.33wt%, Mn: 1.34wt%, Sc: 0.18wt%, La: 1.53wt%, unavoidable impurities ≤ 0.05wt%, and the balance is Al; the other operating steps and parameters remain unchanged.

[0039] Comparative Example 14 Compared with Example 4, the difference of Comparative Example 14 is that the aluminum alloy plate does not include La element, and includes the following components by mass percentage: Si: 0.75wt%, Mg: 2.40wt%, Mn: 1.40wt%, Re: 1.4wt%, Sc: 0.18wt%, unavoidable impurities ≤ 0.05wt%, and the balance is Al; the other operating steps and parameters remain unchanged.

[0040] Test Example 1 Referring to GB / T 22639-2022, the aluminum alloy sheet products prepared in Examples 4-6 and Comparative Examples 11-14 were tested for their anti-exfoliation corrosion performance. The test results are shown in Table 1.

[0041] Table 1

[0042] It can be seen from Table 1 that the aluminum alloy plate prepared in the present invention has excellent corrosion resistance.

[0043] Test Example 2 Friction and wear test: The intermediate alloys obtained in step S3 of Examples 4-6 and Comparative Examples 6-10 were cut into 12mm×12mm×4mm cuboids respectively, and then polished and coated with lubricant in step S4. Meanwhile, heating and heat preservation were not performed in step S4, and the intermediate alloys were pressed by a hydraulic press to obtain the samples. Taking Example 4 as an example, steps S1 to S3 remained unchanged, and step S4 was as follows: S4, cutting the intermediate alloy into 12mm×12mm×4mm cuboids and polishing the surface thereof, and coating 0.2mm of the lubricant obtained in Example 2 at room temperature after polishing, to obtain the samples.

[0044] The two 12mm×12mm surfaces of the sample were water-grinded using sandpaper from coarse to fine until the two surfaces were parallel and smooth. Lubricant was applied to the surface of the sample and the wear rate was tested on the HSR-2M reciprocating friction and wear tester. The wear rate calculation formula is as follows: ; Where m0 is the mass of the sample before the wear test, m1 is the mass of the sample after the wear test, ρ is the density of the sample, W is the load of the wear test, and L is the total length of reciprocating wear; At the same time, the surface wear marks of the specimens after the friction and wear test were observed; The test results are shown in Table 2.

[0045] Table 2

[0046] It can be seen from Table 2 that, under the process of the present invention, the wear of the tool on the intermediate alloy during the pressing process can be reduced, thereby improving the quality of the finished aluminum alloy sheet and increasing its surface aesthetics.

[0047] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0048] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. Corrosion-resistant aluminum alloy sheet for new energy vehicle batteries, characterized in that: The aluminum alloy sheet comprises the following components by mass percentage: Si: 0.50-1.00wt%, Mg: 1.80-2.20wt%, Mn: 1.10-1.20wt%, Re: 0.5-1.0wt%, Sc: 0.15-0.20wt%, La: 0.60-1.20wt%, unavoidable impurities ≤0.05wt%, and the balance is Al.

2. A process for preparing the corrosion-resistant aluminum alloy sheet for new energy vehicle batteries as claimed in claim 1, characterized in that: The specific steps include: S1. According to the composition and proportion of the above aluminum alloy plates, industrial aluminum ingots, magnesium ingots, Al-10wt.%Si master alloy, Al-15wt.%Mn master alloy, Al-2.0wt.%Sc master alloy, Al-10wt.%La master alloy, and Al-10wt.%Re master alloy are weighed, and the surface oxide scales are removed, dried, and preheated respectively; S2, the furnace body is temperature-controlled to add the preheated industrial aluminum ingot and Al-15wt.%Mn master alloy, and the alloy is melted and kept warm. After the insulation is completed, the furnace body is temperature-controlled to add Al-10wt.%Si master alloy, Al-2.0wt.%Sc master alloy, Al-10wt.%La master alloy and Al-10wt.%Re master alloy, and the alloy is melted and kept warm for the second time. The furnace body temperature is maintained, and the magnesium ingot wrapped in aluminum foil is added to melt to obtain alloy liquid; S3, the alloy liquid is subjected to slagging, refining, degassing, temperature control and heat preservation, and the alloy liquid is cast into a preheated warm mold, cooled, taken out and air-cooled to obtain an intermediate alloy; S4. Grind the surface of the intermediate alloy, apply lubricant at room temperature and heat it for insulation. After the insulation is completed, use a hydraulic press to press the intermediate alloy according to customer requirements to obtain the finished aluminum alloy sheet.

3. The preparation process of the corrosion-resistant aluminum alloy sheet for new energy vehicle batteries according to claim 2, characterized in that: In step S2, the temperature of the first temperature control of the furnace is 730-740°C; the temperature of the first melting and heat preservation is 20-30min; the temperature of the second temperature control is 700-710°C; the temperature of the second melting and heat preservation is 20-30min.

4. The preparation process of the corrosion-resistant aluminum alloy sheet for new energy vehicle batteries according to claim 2, characterized in that: The temperature of the temperature control and insulation in step S3 is 695-700°C, and the time is 30-40 minutes; the cooling time is 10-15 minutes.

5. The preparation process of the corrosion-resistant aluminum alloy sheet for new energy vehicle batteries according to claim 2, characterized in that: The heating and heat preservation in step S4 is heating to 680-700° C. and heat preservation for 20-40 minutes; the coating thickness of the lubricant is 0.1-0.2 mm.

6. The preparation process of the corrosion-resistant aluminum alloy sheet for new energy vehicle batteries according to claim 2, characterized in that: The preparation process of the lubricant in step S4 is: A1, formamide and dopamine hydrochloride are mixed uniformly and stirred once, after the stirring is completed, N, N-diethylethylamine is added and stirred twice, hexadecane bromide is added and stirred three times, the pH value of the solution is adjusted, deionized water is added, filtered, the filter residue is washed, trishydroxymethylaminomethane hydrochloride and coconut oil fatty acid diethanolamide are added to the washed filter residue, mixed uniformly and ultrasonically stirred to obtain a coating solution; A2, mixing aluminum sol, silica sol and deionized water uniformly and stirring, filtering, taking the filter residue for washing, to obtain a mixture A, mixing the mixture A and anhydrous ethanol uniformly and stirring, temperature-controlled hydrothermal treatment, cooling, to obtain a mixture B; A3, mixing the coating liquid and the mixed material B, stirring, filtering, taking the filter residue and washing it with deionized water for 3-5 times to obtain composite particles; A4. Mix the base oil, composite particles and surfactant, stir for 20-30 minutes and then ultrasonically oscillate for 20-30 minutes to obtain a lubricant.

7. The preparation process of the corrosion-resistant aluminum alloy sheet for new energy vehicle batteries according to claim 6, characterized in that: The usage ratio of dimethylformamide, dopamine hydrochloride, N,N-diethylethylamine, hexadecane bromide, deionized water, trishydroxymethylaminomethane hydrochloride and coconut oil fatty acid diethanolamide in step A1 is 3-3.2mL: 0.2-0.3g: 0.2-0.22mL: 0.5-0.55mL: 2-2.5mL: 100-110mL: 2-3mL.

8. The preparation process of the corrosion-resistant aluminum alloy sheet for new energy vehicle batteries according to claim 6, characterized in that: In step A2, the mass ratio of the aluminum sol, silica sol and deionized water is 1.5-2:1:2.5-3; the mass ratio of the mixture A and anhydrous ethanol is 1:150-160mL.

9. The preparation process of the corrosion-resistant aluminum alloy sheet for new energy vehicle batteries according to claim 6, characterized in that: The dosage ratio of the coating liquid and mixed material B in step A3 is 100-105 mL: 1-1.2 g.

10. The preparation process of the corrosion-resistant aluminum alloy sheet for new energy vehicle batteries according to claim 6, characterized in that: The mass ratio of the base oil, the composite particles and the surfactant in step A4 is 93-96:3-5:1-2.

Citation Information

Patent Citations

  • Efficient wiredrawing fluid containing silica solution

    CN103966003A

  • Die-castable alloy containing aluminum, magnesium, silicon, manganese and rare earth

    CN104789825A

  • High-strength-toughness and heat-resistant Al-RE-Y-Zr alloy suitable for pressure casting and preparation method thereof

    CN111411268A

  • Corrosion-resistant aluminum alloy die casting

    CN113046605A

  • Micro-alloyed non-heat-treated high-toughness die-casting aluminum alloy and preparation process thereof

    CN113444929A